What is being discussed in the UNCITRAL: evolution or revolution in the investor-State dispute - Fernández Masiá, Enrique; Salvadori, Margherita (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The main initiative to reform the system of investor-State dispute settlement is being debated by Working Group III appointed by the UNCITRAL. Specific proposals for a procedural and institutional reform of the system are being discussed. As concerns the institutional reform, the EU proposes the establishment of a multilateral investment court, which would break the current ad hoc-based system. Independent from these proposals, there appears to be a growing consensus on the establishment of an Advisory Centre on International Investment Law, which could address the issue of costs and duration of procedures, enhance access to justice issues, apart from improving the future treaty law-making.
Keywords: Investor-State Arbitration; UNCITRAL Working Group III; Multilateral Investment Court; Appellate Mechanism; Advisory Centre